TANGGUNG JAWAB HUKUM INFLUENCER ATAS PRODUK ILEGAL: KAJIAN HUKUM PERIKATAN DAN TINDAK PIDANA ITE - Teguh Wicaksono; Fathol Bari; Yulius Efendi (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
The phenomenon of the increasing number of influencers promoting products through social media has raised legal issues when the advertised products turn out to be illegal or harmful to consumers. This study examines the legal liability of influencers from the perspective of contract law under the Indonesian Civil Code (KUHPerdata) and criminal provisions under the Law on Electronic Information and Transactions (ITE Law). Using a normative juridical approach, this study finds that influencers may be held civilly liable for breach of contract if they fail to exercise due diligence in promotional agreements. On the criminal side, the promotion of illegal products may be subject to sanctions under Article 45A of the ITE Law if it fulfills the element of spreading false or misleading information. Therefore, more comprehensive regulations are needed to clarify the legal status of influencers as legal subjects with ethical and legal obligations in the digital sphere.